THE HEART AND ITS POWER: A VIEW THROUGH THE LENS OF FOLK WISDOM (Modern American Journal of Medical and Health Sciences, 2025)
This article, along with the valuable insights of great Uzbek medical scientists, examines the work of the heart – one of the body's organs that has acquired vital significance in human life.